Computerizing Primary Schools in Rural Kenya: Outstanding Challenges and Possible Solutions - Ogembo, Javier Gordon; Ngugi, Benjamin; Pelowski, Matthew (The Electronic Journal of Information Systems in Developing Countries, 2012)
This paper investigates the outstanding challenges facing primary schools’ computerization in rural Kenya. Computerization of schools is often envisaged as a ‘magic’, or at least a particularly efficient, solution to many of the problems that developing countries face in improving primary school education. However, while a great deal of consideration is given to the technical issues surrounding computer implementation, government policy makers, administrators, aid organizations and individuals participating in school computerization programs often have not carefully considered the contextual questions surrounding this endeavour. Specifically: 1.) what problems do rural schools actually want to solve with computerization; 2.) is computerization the most important priority for rural schools; 3.) are schools ready, in terms of infrastructure, for a computer in the classroom; or 4.) might there be better avenues for implementing access to the benefits of the digital age? These questions and the issue of school computerization are considered via results from a survey of thirty-seven rural Kenyan primary public schools. Results indicate that, while all schools had low ICT status making them primary targets for computerization, only eleven percent had at least one ICT compliant teacher, of which all were considered to require further training. In addition we found inadequate infrastructural preparedness – lack of access to electricity, internet; no classroom computer space, few desks, secure walls and protective roofing – posing severe challenges to the outstanding conception of computerization. We consider these results and make recommendations for better adapting programs for computer introduction, and also suggest the use of new innovative devices, such as cell phones, which might already have overcome many of the technical challenges found.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1002/j.1681-4835.2012.tb00371.x KerkoCite.ItemAlsoKnownAs: 10.1002/j.1681-4835.2012.tb00371.x 10/gf7gs8 2339240:33SJHXL4 2405685:NMZU3HHJ
Keywords: ICT; cell phone; classrooms; computerization; primary schools; techno-literacy

Challenges Facing Adoption of Information Communication Technology (ICT) In Educational Management in Schools in Kenya - Kipsoi, Emmy; Chang'ach, Dr; Sang C, Hellen (Journal of Sociological Research, 2012)
ICT has contributed greatly to educational management in schools globally (Zhao and Frank, 2003). However, in Kenya schools hardly use ICTs to manage the quality of output, or to raise teacher productivity, or to reduce costs through analyzing spending. This is attributed to a myriad of challenges facing most schools in Kenya with regard to adoption of ICTs in educational management. This has resulted to a slow rate of adoption of technology despite its promise and potential for use in educational management in schools. As such, this paper analyses the lethargy that has surrounded education management in schools with respect to acquisition of Information Communication Technology. Education and training sector has a major role to play in the implementation of the proposed ICT policy. First, the sector itself is a major user of ICT, not only in education, training and research but also in the management of the sector. The paper argues that ICT policies must be dynamic, cost-effective, adaptable, and differentiated between sectors and between the various segments of educational management in order to contribute effectively to education management. The recommendations of this paper provide a basis for the urgent need for the integration of ICTs in educational management in schools in Kenya.
KerkoCite.ItemAlsoKnownAs: 10.5296/jsr.v3i1.1882 2339240:RXCIEA2R 2405685:EMUX9EK9

An E-Learning Approach to Secondary School Education”: E-Readiness Implications in Kenya - Redempta, Kiilu (Journal of Education and Practice, 2012)
Information and Communication Technology (ICT) has the potential to enhance access, quality, and effectiveness in education. This paper examines the E-readiness implication on the adoption of e-learning in secondary schools in Kenya. The paper provides an opportunity for reflection on e-learning adoption and the potential role ICT can plays in education. The review has established that up to date, less than 10% of secondary schools in Kenya offer computer studies as a subject in the curriculum despite its perceived potential. The few schools that have an ICT programme limit the number of candidates who take up the subject considering it a specialty irrespective its being an essential subject as other compulsory subjects like Mathematics and Languages. Whereas the processing of information to build knowledge is one of the essential literacy skills vital for the workforce in the 21st century, it is often overlooked in current educational practices. the question of ereadiness of Kenyan schools cannot be overlooked if Kenya plans to use education as a platform for becoming an e-society of the 21st century as envisaged in Vision 2030.Therefore, it is imperative that E-Readiness issues be effectively addressed lest new technology introduced further marginalizes the already deprived Kenyan children. Desktop review of relevant literature was guided by Current Situation Analysis (CSA) which is equivalent to Strength, Weakness, Opportunities and Threats (SWOT) Analysis.
KerkoCite.ItemAlsoKnownAs: 2339240:QGAYFNJL 2405685:74DSLY4X
Keywords: ⛔ No DOI found

Teachers' professional development in a challenging educational context – a study of actual practice in rural western Kenya - Onguko, Brown (University of Calgary, 2012)
This research adopted a design research approach, utilizing a mixture of methods including narratives, ethnographic observations, qualitative interviews and documentation of design artifacts. It was implemented in a challenging context in Western Kenya. The first research question for this study was: How might professional development (PD), offered through a blended learning approach and delivered by appropriate technologies, inform potential change to teaching practice in a challenging context in Kenya? Research question two sought to understand the implications of the professional development implemented in this study for teachers and professional development teachers (PDTs). Question three sought to understand the sustainability and scalability of the professional development approach The theoretical framework informing this research is based on activity theory- a needs-driven and goal directed process through tool mediation, and entails division of labor and isolation of partial tasks in a community of relationships (Vygotsky, 1978; Leont’ev, 1978; Engestrom, 1987; 1999; 2000; 2008). Key features of activity theory are active engagement and social interaction, which enabled teachers to collaboratively work with each other, studying through appropriate technologies to inform their teaching practices. Based on a review of literature, interviews with teachers and observation of teachers during face-to-face meetings in professional development and in their classroom practice, this study suggests that teachers in a challenging context can inform potential change to their teaching as a result of participation in locally developed content, delivered through blended learning on appropriate technologies. This study observes that through self-directed study on tablets, and occasional face-to-face interaction, teachers can transform into a community of learners that support each other in planning for their lessons. Content development involving local experts is critical to such interventions in challenging contexts, while drawing from global web content, harnessing open educational resources and being sensitive to local culture. Reflective conversations, professional dialogues and technology stewardship were all critical in informing teachers’ practice.
Publisher: Education KerkoCite.ItemAlsoKnownAs: 10.11575/PRISM/27984 2339240:DG2D5LEQ 2339240:HFGVU85N 2405685:3GUCVMD2 2405685:AJ9GX7EE 2534378:9XFBBTYJ 2534378:SQ7895I3
Keywords: __:import:01; __:match:final; __:matched; __:study_id:2457443; __finaldtb; ⛔ No DOI found

Research methods dictionary - Mugenda, Olive M; Mugenda, Abel G (Kenya Arts Press, 2012)
KerkoCite.ItemAlsoKnownAs: 2405685:HQRL48EG

Effects of Special E-Learning Program on Hearing-Impaired Learners' Achievement and Perceptions of Basic Geometry in Lower Primary Mathematics: - Kiboss, Joel Kipkemboi (Journal of Educational Computing Research, 2012)
Achievement in mathematics is an issue of great concern not only to students and parents but also to employers and researchers in Kenya. This is because the Ken...
Sage CA: Los Angeles, CA shortDOI: 10/ggdtp3 KerkoCite.ItemAlsoKnownAs: 10.2190/EC.46.1.b 10.2190/ec.46.1.b 10/ggdtp3 2339240:E2A49LQS 2339240:SRIBPMIE 2405685:TBHFERAU 2405685:Z3BJFVR2

Challenges and strategies of working with learners with low vision: Implications for teacher training - Yalo, J. A.; Indoshi, F. C.; Agak, J. O. (Educational Research and Reviews, 2012)
Learners with low vision can be trained to increase their visual functioning through a planned programme of visual experiences. Such a low vision training programme was introduced in Kenya in 1994. However, despite its implementation over the last 15 years, challenges still persist among teachers who work with such learners. The purpose of this study was to document challenges that learners with low vision have on teachers’ performance when teaching learners with low vision in special primary schools for the visually impaired in Kenya. The study was carried out in 6 schools for the visually impaired respondents in the study including 78 teachers survey through questionnaire and observation. The study established challenges faced by teachers as lack of appropriate devices for learners, lack of adequate training of teachers and lack of regular teacher auditing. Strategies suggested to address the challenges were supply of low vision devices, low vision teams based at each school reconstituted to provide co-ordinated learning support and regular case conferencing be mounted to provide teacher support.
KerkoCite.ItemAlsoKnownAs: 10.5897/ERR10.100 2339240:B8RGF7UM 2405685:ZSVGWH7J

Context and Appropriate Technology: The Unavoidable Partnership - Onguko, Brown (Proceedings of the European Conference on e-Government, ECEG, 2012)
Teachers in rural parts of Kenya lack opportunities for professional development (PD). In addition, the teachers have no access to eLearning opportunities like their colleagues in urban parts. Among the factors that do not favor Kenyan rural teachers’ access to PD through eLearning include: lack of access to relevant technologies and lack of electricity. This paper shares research findings on provision of teachers’ PD through a blended learning approach, utilizing appropriate technologies in a rural school in western Kenya. Ten teachers and two Professional Development Teachers (PDTs) participated in this research. In the study, teachers’ needs assessment was done, to inform the instructional design on the topic: How to teach a large class of mixed ability students. The PD was implemented by engaging teachers in a variety of activities including: pairs of teachers collaboratively using a tablet to access self-study content; teachers studying through multimedia content; teachers planning and delivering lessons using activity-based learning and cooperative learning approaches; and PDTs and teachers participating in fortnightly face-to-face meetings. The findings of the study suggest that teaching practices of rural educators can be improved working with local experts to create locally-relevant content for needs-based PD, implemented in a blended learning approach while providing technology stewardship. Teachers accessed and studied through offline content; planned for and implemented cooperative learning and activity-based learning in lessons, using locally available materials; engaged in reflective conversations on successes and challenges; and spontaneously engaged in very lively professional dialogues. While teachers appreciated that it took long to prepare for active learning lessons, it was less strenuous to implement the lessons, because the students took responsibility for their own learning.
KerkoCite.ItemAlsoKnownAs: 2339240:24H28YGJ 2339240:ISIT39J6 2405685:5KI53BLU 2405685:W7KJBF6N 2405685:X3EGT59M 2405685:ZHM4CF5K 2534378:7IHB745E 2534378:SU4VP6FM
Keywords: __:import:01; __:match:final; __:matched; __:study_id:2096499; __finaldtb; ⛔ No DOI found